Demonstrative Manufacturing System Controlled by MES Utilizing AAS - Černocký, P.; Arm, J. (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2022)
This work examines today's modern possibilities for production management. More specifically, we focus on MES (Manufacturing Execution Systems) and its integration within the concept of industry 4.0 using AAS (Asset Administration Shell). It also describes a specific integration for a simple virtual line designed in ABB RobotStudio, which is first controlled using MES and then the production is encapsulated using AAS. The AAS is then supposed to interact with ERP (vertical integration) and also with suppliers and other manufacturing units (horizontal integration).
Keywords: MES; AAS; IMES; RobotStudio; virtual factory; OPC UA